Why Don't We Study Laziness? A Bibliometric Analysis of Terminological Avoidance of a Folk Concept - Syahid Izharuddin Lubis; Muhammad Ikbal Wahyu Sukron; Kahfi Hizbullah (Jompa Research and Development, 2026)
The concept of laziness is often avoided in science because it seems to carry negative connotations, despite its frequent use in everyday life. This study aims to present a bibliometric analysis of the topic of laziness. 2,336 articles on laziness published from 1985 to 2025 were analyzed using bibliometric techniques to uncover research trends over 40 years. The analysis procedure began by searching for articles on the topic of laziness using various keywords in the Scopus search database. The search results were then cleaned in OpenRefine to detect ambiguous keywords and processed in VOSviewer, a software tool for conducting bibliometric analysis. The analysis focused on several aspects, such as keyword relevance, author affiliation, the most relevant authors to the topic, and citation analysis. The analysis results were visualized using VOSviewer to provide recommendations for future research on the laziness variable.